2016
DOI: 10.1007/s11367-016-1146-1
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle impacts of topsoil erosion on aquatic biota: case study on Eucalyptus globulus forest

Abstract: Purpose This study illustrates the applicability of a framework to conduct a spatially distributed inventory of suspended solids (SS) delivery to freshwater streams combined with a method to derive site-specific characterisation factors for endpoint damage on aquatic ecosystem diversity. A case study on Eucalyptus globulus stands located in Portugal was selected as an example of a land-based system. The main goal was to assess the relevance of SS delivery to freshwater streams, providing a more comprehensive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Núñez et al (2013) determined effects to NPP, but a solid step from NPP to biodiversity is still lacking. When knowing the amount of soil entering specific water systems, the framework of Quinteiro et al (2015Quinteiro et al ( , 2017 can be used to derive impacts on freshwater biota. Another option is to determine erosion as damage to natural resources, within that area of protection.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Núñez et al (2013) determined effects to NPP, but a solid step from NPP to biodiversity is still lacking. When knowing the amount of soil entering specific water systems, the framework of Quinteiro et al (2015Quinteiro et al ( , 2017 can be used to derive impacts on freshwater biota. Another option is to determine erosion as damage to natural resources, within that area of protection.…”
Section: Applicationmentioning
confidence: 99%
“…Quinteiro et al (2015) determined CFs for effects of suspended solids on freshwater biota in Europe, but did not base their calculations on actual erosion rates. In a recent case study, Quinteiro et al (2017) showed the applicability of their work for erosion impacts of Eucalyptus globulus stands in Portugal. However, there are no CFs available for erosion in LCA on a grid-specific level worldwide, specifically including potential effects of agricultural management and crop type, up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion is one of the most important environmental issues in the world (Yin and Li 2001). Soil erosion hazards involve damaging the aquatic and terrestrial environment by reducing nutrients, increasing runoff and affecting aquatic life (Langdale and Shrader 1982;Pimentel and Burgess 2013;Quinteiro et al 2017;Mamedov and Levy 2019). Soil erosion is divided into two major groups of water and wind erosions.…”
Section: Resultsmentioning
confidence: 99%
“…This can be accomplished by applying a life cycle assessment (LCA)-based methodology, which has been widely used to assess the environmental impacts of forest-based products (e.g. Dias, 2014;Dias and Arroja, 2012;González-García et al, 2014;Quinteiro et al, 2016;.…”
Section: A C C E P T E Dmentioning
confidence: 99%